2005
DOI: 10.1093/eurheartj/ehi411
|View full text |Cite
|
Sign up to set email alerts
|

Favourable clinical outcome in patients with cardiogenic shock due to fulminant myocarditis supported by percutaneous extracorporeal membrane oxygenation

Abstract: In patients with fulminant myocarditis, percutaneous ECMO is a highly effective form of a haemodynamic support. Once a patient recovers from inflammatory myocardial damage, the subsequent clinical outcome is favourable, similar to that observed in patients with acute non-fulminant myocarditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
134
2
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 202 publications
(156 citation statements)
references
References 30 publications
12
134
2
8
Order By: Relevance
“…The cause of acute myocarditis often remains undetermined, but investigations have indicated that viruses represent the most frequent agent [1-3, 14, 15]. Endomyocardial biopsy is considered the gold standard diagnostic tool, although this procedure remains largely underused and has shown low negative predictive value [1,2,13,15]. In our series, one-fourth of the patients had endomyocardial biopsy performed, and acute myocarditis was confirmed in all patients.…”
Section: Commentmentioning
confidence: 60%
See 4 more Smart Citations
“…The cause of acute myocarditis often remains undetermined, but investigations have indicated that viruses represent the most frequent agent [1-3, 14, 15]. Endomyocardial biopsy is considered the gold standard diagnostic tool, although this procedure remains largely underused and has shown low negative predictive value [1,2,13,15]. In our series, one-fourth of the patients had endomyocardial biopsy performed, and acute myocarditis was confirmed in all patients.…”
Section: Commentmentioning
confidence: 60%
“…The clinical scenario of AFM may be characterized by a self-limiting form with rather rapid cardiac recovery and excellent early and mid-term prognosis [1,2,13,15]. On occasion, however, a more malignant course might occur with refractory hemodynamic compromise, ultimately leading to patient death if no mechanical cardiocirculatory support is promptly instituted [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Commentmentioning
confidence: 99%
See 3 more Smart Citations